Inhibition of browning in cherimoya ‘Fino de Jete’ peel by application of 6-bencylaminopurine - Morales P, Aaran A. (2015)
The cherimoya (Annona cherimola Mill.) fruit is climacteric and has a very short postharvest life; the symptoms of senescence include peel browning and fruit softening. The objective of this research was to evaluate the effect of application of 6-benzylaminopurine (BAP) in the postharvest life of cherimoya fruit ‘Fino de Jete’. Fruits were randomly selected from the middle and basal part of six trees. BAP was applied at 1.0 mM or 0 mM in every of two dates, that is 8 or 15 days before harvest (DAC). After harvest, fruits were transported for 1.5 h and stored in two different temperatures, refrigerated (TR) (6 °C) or room temperature (TA) (16 ± 2 °C). Every third day, from 1 to 15 day after harvest (DDC), they were analyzed in relation to weight loss, color L*, a* and b*, and fruit firmness and deformation. In TA, the fruits treated with 1 mM BAP in both, 8 or 15 DAC retained peel color L* over 35% (ρ ≤ 0.05) in relation to control.